The Community Empowerment of Bandarharjo Village, North Semarang in the Stunting Awareness Community Movement - Agnes Dwi Safarina; Nirmala Al Fatiah; Nabila Azzahra Luthfiah; Kirana Rannoe Tirta; Adhisti Lutfia Hanan; Ari Yuniastuti (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2022)
The high rate of stunting in toddlers is one of the health problems in Bandarharjo Village, North Semarang. One of the efforts to overcome stunting is through community empowerment to support health independence. Educational and training activities to improve knowledge and attitudes of the community so that they care about stunting are carried out from February to May 2022, including assistance for posyandu activities, mentoring for PMT distribution, and socialization related to nutrition, health, and parenting to mothers and caregivers. The results of this activity include mothers and caregivers knowing food guidelines and nutritious eating menus so that children are not malnourished and avoid stunting, correct parenting for toddlers and a clean and healthy environment. It is hoped that this activity will have implications for public awareness of stunting. Keywords: stunting, emporwment, training